Emergence of ferromagnetism and Jahn-Teller distortion in LaMn1−xCrxO3 (x < 0.15) - Ramos, Aline Y. (2013)
The emergence of a ferromagnetic component in LaMnO3 with low Cr-for-Mn substitution has been studied by x-ray absorption spectroscopy and x-ray magnetic circular dichroism at the Mn and Cr K edges. The local magnetic moment strengths for Mn and Cr are proportional to each other and follow the macroscopic magnetization. The net ferromagnetic components of Cr3+ and Mn3+ are found antiferromagnetically coupled. Unlike hole doping by La site substitution, the inclusion of Cr3+ ions up to x=0.15 does not decrease the Jahn-Teller (JT) distortion and consequently does not significantly affect the orbital ordering. This demonstrates that the emergence of the ferromagnetism is not related to JT weakening and likely arises from a complex orbital mixing.